Anaesthetic Management of Emergency Tracheostomy in a Three Years Old Child with Recurrent Laryngeal Papillomatosis: A Case Report - Deb, Dr. Prakash; Yunus, Dr. Md.; Sharma, Dr. Narendra Kumar (International Journal of Innovative Research in Medical Science, 2020)
Juvenile onset recurrent laryngeal papillomatosis is a condition which requires multiple surgical excisions to maintain airway patency. However, if neglected may lead to airway compromise requiring emergency tracheostomy and anaesthetic management in such paediatric case is challenging. Awake tracheostomy is difficult and risky in children who are usually restless and uncooperative. Also induction of anaesthesia by intravenous or inhalational route pose a threat to the loss of airway muscle tone & patency. We present here a three years old child with recurrent laryngeal papillomatosis who landed up with emergency tracheostomy for severe stridor where the passage of even the smallest size endotracheal tube would not be possible however emergency tracheostomy could be safely done by inhalational induction maintaining spontaneous ventilation. Such paediatric case where even endotracheal tube could not be passed has been rarely reported. Also literature on anaesthetic management of paediatric emergency tracheostomy is sparse.